2020
DOI: 10.32890/ijms.26.2.2019.10518
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Integration and Supply Chain Performance: The Role of Knowledge Sharing as a Mediator

Abstract: The purpose of this paper is to examine the mediating role of knowledge sharing in the relationship between supply chain integration and supply chain performance. This study used a survey questionnaire for a sample size of 277 managers from various sectors in the manufacturing industry in Jordan.  This study utilised PLS Structural Equation Modeling for testing the hypothesis.  The finding indicates a significant positive relationship between supply chain integration and supply chain performance and that knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Moreover, the result output exposed that the link of SCMP with OP was partially mediated by KM capability. The similar results have also been revealed by Isa and Dweiri (2019). However, the study of Isa and Dweiri (2019) found that KM mediates the relationship between supply chain integration and supply chain performance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, the result output exposed that the link of SCMP with OP was partially mediated by KM capability. The similar results have also been revealed by Isa and Dweiri (2019). However, the study of Isa and Dweiri (2019) found that KM mediates the relationship between supply chain integration and supply chain performance.…”
Section: Discussionsupporting
confidence: 82%
“…The similar results have also been revealed by Isa and Dweiri (2019). However, the study of Isa and Dweiri (2019) found that KM mediates the relationship between supply chain integration and supply chain performance. This way, the finding of the instant study is novel in FMCG context of a developing country.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation